Reliability of the Main 2D Kinematic Variables of Running Evaluated Categorically in Amateur Runners, Aged 18 to 55 Years - Annie V Stappung; Paulina M Espinoza; Matilda J Letelier; Felipe H Palma (International Journal of Sports Physical Therapy)
# Background Running offers numerous health benefits, yet the prevalence of running-related injuries remains perfect. Evaluating running biomechanics through kinematic variables has gained attention due to their association with injuries. Currently, 3D video analysis is considered the gold standard, however, its complexity and cost limit widespread use. Consequently, 2D kinematic analysis using standard cameras has become popular, although research on its reliability is lacking. Hypothesis/Purpose: The purpose of this study was to evaluate the reliability of the main kinematic variables of running, assessed categorically using 2D video analysis, in amateur runners aged 18 to 55 years.